2019
DOI: 10.3390/plants8110495
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Senescence: The Chloroplast Connection Comes of Age

Abstract: Leaf senescence is a developmental process critical for plant fitness, which involves genetically controlled cell death and ordered disassembly of macromolecules for reallocating nutrients to juvenile and reproductive organs. While natural leaf senescence is primarily associated with aging, it can also be induced by environmental and nutritional inputs including biotic and abiotic stresses, darkness, phytohormones and oxidants. Reactive oxygen species (ROS) are a common thread in stress-dependent cell death an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 145 publications
1
26
0
Order By: Relevance
“…Overexpressing OsGLK1 in WT plants also led to abnormal plastid development and tapetum degradation. Plastids differentiate into elaioplasts during tapetum development, a process required for the phase transition 46,47 . Our findings suggest that the fluctuating expression of OsGLK1 is required for the differentiation of plastids into elaioplasts.…”
Section: Osppr2-1 Regulates Osglk1 Expression To Mediate Tapetum Devementioning
confidence: 99%
“…Overexpressing OsGLK1 in WT plants also led to abnormal plastid development and tapetum degradation. Plastids differentiate into elaioplasts during tapetum development, a process required for the phase transition 46,47 . Our findings suggest that the fluctuating expression of OsGLK1 is required for the differentiation of plastids into elaioplasts.…”
Section: Osppr2-1 Regulates Osglk1 Expression To Mediate Tapetum Devementioning
confidence: 99%
“…By comparing scions from the juvenile and the adult phases of the same hybrid, we observed that the photosynthetic properties did not vary significantly between ontogenetic phases (Figure 1). Therefore the adult-phase-specific plastid H 2 O 2 accumulation may be attributed to shift in scavengers or other factors, excluding changes in photosynthetic rate, because developmental cues like vegetative phase change or physiological aging accelerates ROS production [58].…”
Section: The Accumulation Of Chloroplastic H 2 O 2 In the Adult Phase Is Due To Decreased Scavenging Capacity Rather Than Higher Photosynmentioning
confidence: 99%
“…Leaf senescence is a highly regulated developmental process and triggered by diverse environmental factors (Woo et al, 2019 ). As a sophisticated biological event, leaf senescence comprises multidimensional alterations in cell structure, metabolism, and expression of genes (Mayta et al, 2019 ). Organelles and macromolecular substances gradually degraded in an ordered manner.…”
Section: Introductionmentioning
confidence: 99%